The Impact of Natural Disasters on Poverty in Rural Area - Muhammad, Fahmi; Qibthiyyah, Riatu Mariatul (Jurnal Ilmu Ekonomi Terapan, 2025)
Objective: This study aims to analyze the impact of natural disasters on household consumption and poverty in rural area, focusing on three major types of disasters: volcanic eruptions, earthquakes, and tsunamis. It addresses the vulnerability of rural communities caused by limited access to insurance, emergency savings, and infrastructure, highlighting the importance of understanding the disaster–poverty nexus to design more effective protection and recovery strategies. Design/Methods/Approach: The analysis employs panel data from the Indonesian Family Life Survey (IFLS) for 2007 and 2014, validated using the Emergency Events Database (EM-DAT). Fixed-effect and logit models are used to estimate the effects of disasters on per capita household consumption and poverty likelihood. This empirical approach allows for identifying both the direct and indirect economic impacts of disasters on rural household welfare. Findings: The results indicate that natural disasters reduce rural households’ per capita consumption by 2.29%. However, this reduction does not always translate directly into poverty; instead, it reflects underlying economic stress that may evolve into long-term poverty if unaddressed. The findings also highlight that savings play a crucial role in mitigating the negative impact of disasters on consumption, underscoring the importance of access to basic financial instruments in enhancing household resilience. Originality/Value: This study contributes by integrating household-level microdata and disaster event data to explore the relationship between natural shocks and rural poverty dynamics. The combined use of fixed-effect and logit models offers a comprehensive understanding of heterogeneity across households and affected regions. Practical/Policy implication: The findings emphasize the need to strengthen simple financial instruments such as savings and community-based microinsurance as part of adaptive and social protection strategies. Policies promoting financial inclusion and localized risk protection systems can enhance household resilience to disasters and reduce the likelihood of long-term poverty traps.